Wolves' Heads and Wolves' Tales: Women and Exile in Bisclavret and Wulf and Eadwacer. (January 2014) - Blud, Victoria
<x content-type="archive" xml:space="preserve">Abstract</x> The werewolf has historically been aligned with the exiled outlaw or bandit in both laws and literature: the man whose death is not punishable by law and may be killed like a wolf. In post-Conquest England, this link was expressed in the decree for outlaws, "let him bear a wolf's head, " a blend of Anglo-Saxon terminology and Norman documentation. Giorgio Agamben's analysis of exile in Homo Sacer takes Marie de France's Bisclavret as an exemplar of the wolfish, outcast life, while in the Old English tradition the elegiac poem Wulf and Eadwacer has been linked with the "wolf's head" image from its earliest studies. However, when the significance of outlawry to these texts is discussed, it is almost exclusively in connection with their male characters (the eponymous Bisclavret and the mysterious Wulf). Here, I focus on the female figures of the texts, with reference to Julia Kristeva's study of the abject (maternal) body, arguing that the unfaithful wife of Bisclavret — disfigured and banished for her misdemeanors — and the female speaker of Wulf and Eadwacer — secluded on an island, neither in nor out of her community — may represent a different kind of exile and perhaps a different kind of "wolf."